Respuesta :
Answer:
[tex]f(x)\rightarrow +\infty\text{ as }x\rightarrow -\infty[/tex]
[tex]f(x)\rightarrow +\infty\text{ as }x\rightarrow +\infty[/tex]
Step-by-step explanation:
Given polynomial function is,
[tex]f(x)=3x^4+2x^2-x[/tex]
Since, the end behavior of a polynomial is same as the end behavior of leading term,
Here, the leading term = [tex]3x^4[/tex]
[tex]\text{As }x\rightarrow -\infty[/tex]
The leading term is positive,
[tex]\text{While, as }x\rightarrow +\infty[/tex]
The leading term is positive,
Hence, the end behavior of the given polynomial is,
[tex]f(x)\rightarrow +\infty\text{ as }x\rightarrow -\infty[/tex]
[tex]f(x)\rightarrow +\infty\text{ as }x\rightarrow +\infty[/tex]
⇒ In the graph of f(x), both ends will go upward.